BODY MASS INDEX, PROTEIN INTAKE AND HAND GRIP STRENGTH AMONG YOUTH - Anna Fitriani; Desiani Rizki Purwaningtyas (Jurnal Kesmas (Kesehatan Masyarakat) Khatulistiwa, 2020)
Hand Grip Strength (HGS) is an indicator of muscle strength tha has been a predictor of physical capacity and long-term health. There has been a a decrease in HGS among youth and is related with several factors such us body mass index (BMI) and protein intake, but the available researches are still inconsistent. This cross sectional study examined the level of HGS and it’s relationship with BMI and protein intake among female college student of UHAMKA Jakarta. HGS were measured by Smedley Dynamometer and were carried out according to the Southampton Protocol. Anthropometric measurements and self 3-day food records were performed to obtain BMI and total protein intake. Chi square test was performed to reveal the difference proportion of low HGS among various groups. The results showed that the average HGS score was 21.70 ± 7.09 kg, of which 48.7% of respondents were classified as low HGS. There was no significant difference of low HGS proportion between normal BMI and abnormal BMI (less and more) (P value = 0.481). However, the proportion of low HGS was significantly higher among those who had deficit protein intake compared to normal (P value = 0,000). Therefore, an adequate protein intake is needed to maintain muscle strength among youth.   Keywords: Muscle strength, hand grip strength, BMI, protein intake, youth